ISOLATION AND CHARACTERIZATION OF ENDOPHYTIC FUNGI FROM CALOTROPIS PROCERA FOR THEIR ANTIOXIDANT ACTIVITY - Nagda, Vipin; Gajbhiye, Archana; Chhatwani, Dinesh Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To investigate the antioxidant activity of methanolic extract of endophytic fungi isolated from Calotropis procera plant. Methods: The endophytic fungi were isolated from explants of leaf, stem, and flower of C. procera on potato dextrose broth (PDB) medium. The fungal isolates were mass cultured in PDB. The methanolic extracts of these fungi were prepared and evaluated for the antioxidant activity by 1,1-diphenyl- 2-picryl-hydrazyl (DPPH) free radical scavenging assay and reducing power assay. The extracts were characterized for the presence of phenolics and flavonoids. Results: A total of 8 endophytic fungi were isolated from C. procera explants. Out of these 8 fungal isolates, the crude extracts of two fungi, i.e. CPIMR-2 and CPIL-1 showed positive antioxidant activity. From the morphological characteristics, the isolates CPIMR-2 and CPIL-1 were identified as Penicillium spp. and Aspergillus spp., respectively. Both the isolates were found to possess antioxidant potential with % inhibition value of 81.16% and 80.97% in the DPPH radical scavenging assay. The phytochemical screening of the methanolic extracts showed the presence of phenolics and flavonoids. The total flavonoids content in Penicillium species and Aspergillus species were found to be 130.50 Î¼g/mg and 94.91 Î¼g/mg of extracts, respectively. The total phenolic content was found to be 9.16 Î¼g/mg and 12.13 Î¼g/mg of extracts in Penicillium species and Aspergillus species, respectively. Conclusions: Endophtyic fungi were found to be present in medicinal value plant C. procera. The probable bioactive component for antioxidant activity possessed by the fungi would be the flavonoids and phenolics. These metabolite produced by endophytic fungi from C. procera need to be explored further as potential source of novel natural antioxidant compound. Keywords: Endophytes, Calotropis procera, Antioxidant, Radical scavenging, Reducing power, Flavonoids.